Glove versus controller: the effect of VR gloves and controllers on presence, embodiment, and cognitive absorption - Palombo, Raphael; Weber, Sebastian; Wyszynski, Marc; Niehaves, Björn (Frontiers in Virtual Reality, 2024)
Introduction: Using our own hands allows us humans to interact with the real world as we have learned from an early age. VR-gloves allow a similar interaction in VR by transferring hand movements through natural mapping. Research outside the VR domain has already shown that this process creates a high level of presence and perceived naturalness. Research in the VR-context on the other hand is still in an early stage and is lacking explorative qualitative research, which follow a human-centered approach to include the direct perceptions of users on mapped controls into system design. Against that background, this research investigates natural mapping in the VR context in a qualitative manner. The study examines how participants experience VR input-devices with different degrees of natural mapping (VR-gloves, Valve index-controller, and HTC Vive-controller) on perceived naturalness, spatial presence, embodiment, and cognitive absorption. Methods: A focus group (N = 20 aged 22 – 36) did the VR experience with the devices and was asked in semi-structured interviews about their experience. Questions focused on perceived naturalness, spatial presence, cognitive absorption, and embodiment with the three devices. Data was analyzed with a qualitative content analysis. Results: Feedback on spatial presence was widely positive for the VR-glove due to the highly natural perceived movement capabilities. Also mapping with the partly mapped index-controller was seen as natural and immersing if the movement matched the operated actions in the system. Participants mainly stated to perceive the highest degree of cognitive absorption and embodiment, while doing the task with the VR-glove. Discussion: The findings indicate, that the natural mapping capabilities of VR input-devices strongly influence spatial presence. The VR-glove stands out while being able to induce a feeling of embodiment in most cases. Furthermore, participants reported a connection between natural mapping and perceived cognitive absorption in the task.